ANALISIS PEMASARAN BAWANG MERAH PADA KELOMPOK TANI FAJAR PAGI DI KELURAHAN OESAO KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Tudua, Putry Jofritiara; Bano, Maria; Chamdra, Santhy (Buletin Ilmiah Impas, 2024)
The profit of shallot farming is not only determined by production but also by the pattern of marketing channels used by farmers. This study aims to determine the marketing function, marketing channels, marketing costs, farmer share, and marketing efficiency level. The research data were obtained by conducting interviews with 20 respondent farmers and 17 traders. The research method used a qualitative descriptive analysis method using predetermined equations. The results showed that there were two shallot marketing channels, namely marketing channel I covering farmers - Kupang City Market retailers - consumers and marketing channel II covering farmers - intermediary traders - Soe retailers - consumers. The total margin on marketing channel I is Rp. 2,000 / kg. farmer share is 2.27%. Marketing channel II total marketing margin of Rp. 6,000/kg, and farmer share of 38.33% The most efficient marketing channel is marketing channel I with an EP value of 12.50%.